High-velocity elastic-band training improves hamstring muscle activation and strength in basketball players - Kamandulis, S.; Janusevicius, D.; Snieckus, A.; Satkunskiene, D.; Skurvydas, A.; Degens, H. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: The aim of this study was use surface EMG activity to assess changes in co-activation of knee flexors and extensors muscle groups during elastic-band exercise after 5 weeks of high-velocity elastic-band training in basketball players. METHODS: College male basketball players (N.=18) were randomly divided into one of two groups: 1) the elastic-band training group performed low-load and high-velocity - lying prone - hamstring curls training three times per week; 2) the control group did not do any training. Pre- and post- training assessment included concentric knee extension and flexion at 60°/s and 240°/s, and the frequency of knee flexion and extension with elastic bands in the prone position. The EMG of the rectus femoris, semitendinosus muscles and the long head of the biceps femoris were assessed during these activities, and 30-m sprint running speed was measured from a stationary start and a running start. RESULTS: It was shown that high-velocity elastic-band training was 1) feasible, 2) increased movement velocity and 3) muscle strength, 4) altered neural control such that excessive lengthening of the hamstring muscle, and hence strain-injuries, may be prevented and 5) improved sprint performance in basketball players. CONCLUSIONS: These results suggest that high-velocity elastic-band training may be a tool to prevent hamstring strain-injuries in basketball players.